Persepsi Orang Tua Dan Siswa Terhadap Pembelajaran Non Formal Di Desa Majanang - Fahri Mulki; Syamsuriyawati; Ernawati (GENIUS: Jurnal Inovasi Pendidikan dan Pembelajaran, 2023)
This research is qualitative research, namely a research procedure that uses descriptive data in the form of written or spoken words from people and also actors who can be observed. This research was conducted in Majannang Village in September 2023. The subjects of this research were 3 parents and 3 students who took part in non-formal learning. Data collection was carried out using questionnaires, interviews, and documentation. Data analysis was carried out by data reduction, data presentation and drawing conclusions. The results of the research are that parents' perceptions of non-formal education are very clearly reflected in the aspects of attention, response, and assessment. Parents really support their children in participating in tutoring. Parents' awareness of the importance of education for children is a priority for the smooth running of children's education. The form of attention that parents can give is to meet the needs of educational facilities and raise children's motivation to acquire knowledge. And students' perceptions of the three indicators, namely attention, response, and assessment, illustrate that on average students strongly agree with the program or method used in non-formal learning. Of the four answer choices provided, namely disagree, disagree, agree, and strongly agree, the average student tends to be at the strongly agree level. This shows that students overall feel very positive and satisfied with the non-formal learning experience they participated in.